KONSTRUKSI SOSIAL ROKOK ELEKTRIK (VAPE) SEBAGAI SUBSTITUSI ROKOK TEMBAKAU BAGI PEROKOK AKTIF DI KOTA DENPASAR - Santana, I Gede Agung Krishna; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The phenomenon of electric cigarette in Denpasar can be analyzed through several research in sociology. This research seeks to discuss and explain the social construction of electrical cigarettes as a substitution to tobacco cigarettes in the area city of Denpasar. This research uses descriptive qualitative research method with analysis of Social Construction theory from Peter L. Bererger and Thomas Luckman as the main theory and society of consumption of Jean Baudrillard as a supporting theory. The relationship between the theory of social construction with the theory of consumption society in this study are interrelated, because the formation of the consumption community in electric cigarettes influenced by the social construction of electric cigarettes through externalization, objectivity, and internalization. The social construction of electrical cigarettes is accepted by society to form a growing consumer society today that society consumption is no longer based on exchange rate or use value, but because of the abstract and constructed value of symbols and values ??of symbols. Based on the results of this reseacrh note that those who are using electric cigarettes not only consume value for use and exchange rates, but to the the exteat that they use electric cigarettes based on the value of signs and symbol values this is finally in the form of following trend, status, expression and luxury lifestyle. Keywords: Social Construction of Electric Cigarettes, Signs Value and symbolic Value.